Global governance, human rights and international law : combating the tragic flaw - Mendes, Errol (Abingdon, Oxon : Routledge, 2014)
'Offering a stimulating introduction to the topic of global governance this book draws together diverse topics in order to clearly establish the links between areas of global governance, the global economy and international law. By drawing on a range of diverse subject areas, Errol P. Mendes argues that the foundations of global governance, human rights and international law are undermined by a conflict, where high ideals and state sovereignties are pitted against destructive self-interest. The book explores how human rights and international law are applied in some of the critical institutions of global governance and in the operations of the global private sector, and how States, institutions and global civil society struggle to fight this'tragic flaw'. The book is brought up to date by considering developments in the importance of bilateral investment treaties; the likely failure of the Doha round of WTO negotiations; the legacy of the 2008 financial crisis; and international peace and security crises in Sri Lanka, North Africa and Georgia and the Russian Federation. With its intensely interdisciplinary approach, this book motivates new thinking in the realm of global governance and international law, and promotes the development of new strategies for how the international community can negotiate between conflicting leadership, national, and organisational values within global institutions. The book will be of interest to students and researchers of public international law, global governance and international trade and economic law'--
The rise of the tragic flaw : challenging the grundnorm of international law and global governance -- The human rights failures of the global trade and financial systems -- Power and responsibility : international law, human rights and the social responsibilities of the global private sector -- Global pluralism : the next stage in global governance, human rights and international law.
Includes bibliographical references and index.
Keywords: International law and human rights